Modeling of the work hardening in magnesium alloy sheets. (January 2016) - Balík, Jaroslav; Dobroň, Patrik; Chmelík, František; Kužel, Radomír; Drozdenko, Daria; Bohlen, Jan; Letzig, Dietmar; Lukáč, Pavel
Abstract: The deformation behavior of rolled Mg–Al–Zn and Mg–Zn–RE (rare earth) sheets after annealing was investigated in tension. The tensile axis was oriented in either the rolling direction (RD) or the transverse direction (TD). The deformation tests of the sheets were accompanied by in situ measurements of the acoustic emission (AE); AE signal analysis correlates the microstructure and the stress-strain curves to possible deformation mechanisms. X-ray diffraction is applied to determine information about the deformation textures both prior to and after the tests. Both texture analysis and AE for different loading and texture conditions suggest that the prismatic slip is dominant in larger deformation stages. A strain hardening model, based on the generalized Kocks-Mecking approach, is fitted to the observed deformation behavior, including the mechanical anisotropy of the Mg alloy sheets. The model enables the determination of the work hardening coefficient, considering the glide obstacles of both dislocation and non-dislocation origin; the distribution of grain orientations is also considered. The work hardening analysis is applied to the late stage of deformation, where twins are included only as non-dislocation barriers for mobile dislocations. Highlights: Mg-based rolled alloys are tensile tested along the rolling and transverse directions. Using textures, the prismatic slip is revealed as dominant in later deformation stages. The work hardening parameters are drawn by fitting of hardening and orientation data. The similitude governed hardening does not occur in the prismatic slip regime. The high intensity of acoustic emission corresponds to other indications of twinning.